KLF12 Aggravates Angiotensin II‐Induced Cardiac Remodeling in Male Mice by Transcriptionally Inhibiting SMAD7 - Min Hu; Shi‐Yu Huang; Yi‐Peng Gao; Yu‐Xin Hu; Sha‐Sha Wang; Teng Teng; Xiao‐Feng Zeng; Qi‐Zhu Tang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Adverse left ventricular remodeling and subsequent heart failure remain a major cause of patient morbidity and mortality worldwide. The KLF family of transcription factors plays crucial roles in heart injury. KLF12 (Krüppel‐like factor 12) is a transcription factor that regulates multiple disease processes, although the specific role of KLF12 in cardiac remodeling remains unclear. Methods and Results In our study, we observed a significant upregulation of KLF12 expression in remodeling hearts. The increased expression of KLF12 primarily originated from cardiac fibroblasts during the fibrotic response induced by angiotensin II. To investigate the effects of KLF12, we performed RNA‐seq and found that KLF12 overexpression significantly upregulated the cardiac remodeling associated pathway. Hence, we generated adult mice with cardiac fibroblast‐specific overexpression of KLF12 using lentivirus or miRNA (miR‐1/133TS) technology. Compared with control mice, KLF12‐miR1/133TS transfected mice exhibited exacerbated cardiac remodeling and function. Mechanistically, we discovered that KLF12 directly binds to the promoter of Smad7, leading to the activation of the TGF‐β (transforming growth factor beta)‐Smad3 pathway. Conclusions In conclusion, KLF12 promoted the development of angiotensin II‐induced cardiac remodeling in male mice. Targeting KLF12 may be a promising therapeutic approach to treat cardiac remodeling.